Speed control of induction motor using fuzzy - Mohd Nazimudin Ibrahim (School of Electrical Systems Engineering, Universiti Malaysia Perlis, 2015)
This dissertation presents a methodology for implementation of a rule based fuzzy logic controller applied to a closed loop volts/hertz single phase induction motor speed control. The induction motor is modelled by using d-q axis theory. The performance of FLC is compared with that of a PI controller. The advantages of the Fuzzy Logic Controller over the conventional controllers are : (i) they are economically advantageous to develop, (ii) a wider range of operating conditions can be covered using FLCs, and initial approximate set of fuzzy rules can be impulsively refined by a self-organizing fuzzy controller. For volts/hertz speed control of the single phase induction motor, a reference speed has been used and the control architecture includes some rules. The errors are evaluated according to the rules in accordance to the defined member functions. The member functions and the rules have been defined using the Fuzzy Inference System (FIS) editor given in Matlab. The system has been simulated in Matlab / Simulink and the results are given. Provide briefing results, analysis and discussed.